2015
DOI: 10.1021/jf505533r
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate Loss by Runoff and Its Relationship with Phosphorus Fertilization

Abstract: The aim of this study was to evaluate the relationship between glyphosate and phosphate fertilizer application and their contribution to surface water runoff contamination. The study was performed in Aquic Argiudoll soil (Tezanos Pinto series). Four treatments were assessed on three dates of rainfall simulation after fertilizer and herbicide application. The soluble phosphorus in runoff water was determined by a colorimetric method. For the determination of glyphosate and aminomethylphosphonic acid (AMPA), a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 19 publications
0
29
0
13
Order By: Relevance
“…Particularly, Aparicio et al (2013), found pesticide levels in surface soil from Buenos Aires province, one of the most important soybean production areas, which ranged between 0.035-1.502 μg/g and 0.299-2.256 μg/g for glyphosate and AMPA, respectively. The relationship of a glyphosate-based commercial product and phosphorus fertilizer application in a runoff experiment was recently evaluated in Aquic Argiudoll soil (Sasal et al, 2015). However, there is no evidence of field studies about glyphosate behavior through soil profile and its potential transport to groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Aparicio et al (2013), found pesticide levels in surface soil from Buenos Aires province, one of the most important soybean production areas, which ranged between 0.035-1.502 μg/g and 0.299-2.256 μg/g for glyphosate and AMPA, respectively. The relationship of a glyphosate-based commercial product and phosphorus fertilizer application in a runoff experiment was recently evaluated in Aquic Argiudoll soil (Sasal et al, 2015). However, there is no evidence of field studies about glyphosate behavior through soil profile and its potential transport to groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…En el periodo julio de 2009 -noviembre de 2012 fueron recolectadas 93 muestras de agua de escorrentía en sistemas agrícolas (Cuadro I): 36 obtenidas mediante la utilización de un simulador de lluvia (Sasal et al 2015; Fig. 2) y 57 en parcelas de escorrentía (con diferentes secuencias de cultivo) recolectadas a posteriori de eventos de precipitación que generan escurrimientos con lluvia natural ; Fig.…”
Section: Recolección De Muestrasunclassified
“…Las mayores concentraciones de glifosato fueron registradas con simulaciones de lluvia de alta intensidad, inmediatamente posteriores a las aplicaciones del herbicida (Sasal et al 2015). …”
Section: Determinación De La Concentración De Glifosato En Muestras Dunclassified
“…Há interação entre a adubação fosfatada e o comportamento do glyphosate no solo (Sasal et al, 2015), além de haver evidências da interação entre o glyphosate e o fósforo do solo sobre a ação do herbicida nas plantas (Clua et al, 2012). Savin et al (2009) observaram alteração significativa na infecção por fungos micorrízicos arbusculares em soja, milho e algodão, resistentes ao glyphosate, submetidos à adubação fosfatada ou não, em solos pobres em fósforo; no entanto, essa alteração pode ser dependente de outras na microbiota do solo, por influência de outros fatores.…”
Section: Introductionunclassified